Engineering Escherichia coli for Efficient Aerobic Conversion of Glucose to Malic Acid through the Modified Oxidative TCA Cycle - Alexandra Yu. Skorokhodova; Anastasiya A. Stasenko; Natalya V. Krasilnikova; Andrey Yu. Gulevich; Vladimir G. Debabov (Fermentation, 2022)
Malic acid is a versatile building-block chemical that can serve as a precursor of numerous valuable products, including food additives, pharmaceuticals, and biodegradable plastics. Despite the present petrochemical synthesis, malic acid, being an intermediate of the TCA cycle of a variety of living organisms, can also be produced from renewable carbon sources using wild-type and engineered microbial strains. In the current study, Escherichia coli was engineered for efficient aerobic conversion of glucose to malic acid through the modified oxidative TCA cycle resembling that of myco- and cyanobacteria and implying channelling of 2-ketoglutarate towards succinic acid via succinate semialdehyde formation. The formation of succinate semialdehyde was enabled in the core strain MAL 0 (∆ackA-pta, ∆poxB, ∆ldhA, ∆adhE, ∆ptsG, PL-glk, Ptac-galP, ∆aceBAK, ∆glcB) by the expression of Mycobacterium tuberculosis kgd gene. The secretion of malic acid by the strain was ensured, resulting from the deletion of the mdh, maeA, maeB, and mqo genes. The Bacillus subtilis pycA gene was expressed in the strain to allow pyruvate to oxaloacetate conversion. The corresponding recombinant was able to synthesise malic acid from glucose aerobically with a yield of 0.65 mol/mol. The yield was improved by the derepression in the strain of the electron transfer chain and succinate dehydrogenase due to the enforcement of ATP hydrolysis and reached 0.94 mol/mol, amounting to 94% of the theoretical maximum. The implemented strategy offers the potential for the development of highly efficient strains and processes of bio-based malic acid production.